PENERAPAN SANKSI PIDANA TERHADAP PEDAGANG KAKI LIMA YANG TIDAK MENJAGA KETERTIBAN DAN KEBERSIHAN LINGKUNGAN DI SEKITAR TEMPAT USAHA BERDASARKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 11 TAHUN 2001 TENTANG PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA - Muhammad Putrapratama; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The growing number of street vendors in downtown areas is incontrollable. A program to comprehensively arrange and guide those street vendors is seriously needed. The existence of street vendors in downtown is one of the factors that leads to the problems such as traffic problem, crime rate, and waste problem. The growing number of street vendors has rushed the local government to make known the Local Regulation Number 11 Year 2001 about The Street Vendor Arrangement and Guidance. Based on the local regulation, the government is expected to control the mushrooming street vendors.Qualitative method was used in the research. During the research, descriptive analysis which is the method to provide systematic, factual, and accurate illustration or description on the data was used. Primary data was obtained from interview and the secondary data was obtained from document, archive, and direct observation to get the real condition of the case. The direct observation was done by involving in the programs of Department of Marketplace like doing the patrol, meeting, and relocation. The data was then analyzed qualitatively in the forms of essay, illustration, and conclusion making of the observed signs.Pekanbaru is a big city which has accommodated its street vendors based on the Local Regulation Number 11 Year 2001 about The Street Vendors Arrangement and Guidance. The regulation sets the place of business, permit, levies, rights, obligations and prohibitions, guidance, and penal provisions related to arrangement and guidance. The obstacle in eradicating the regulation is that the weak supervision from the stakeholders, inconveniently located relocation site, unavailability of transportation facilities, lack of legal awareness, and the economic factors of the vendors like the inability to pay the levy, and from the stakeholders’ point of view which provides less guidance and comprehensive information to the street vendor that results in the vendors who has limited understanding of the dos and don’ts in trading.The recommendations to enhance the ability in doing the responsibilities, the stakeholders should be professional, highly-commited, honest, responsible, and democratic so incompetent stakeholders are not found during the implementations of local regulation. The guidance, supervision, and quality controlling by socializing and doing the patrol should be enhanced.Keywords: Sanctions, Street Vendors, Local Regulation Number 11 Year 2001 About The Street Vendor Arrangement and Guidance